2017
DOI: 10.1016/j.toxlet.2016.11.015
|View full text |Cite
|
Sign up to set email alerts
|

The endocrine disrupting potential of monosodium glutamate (MSG) on secretion of the glucagon-like peptide-1 (GLP-1) gut hormone and GLP-1 receptor interaction

Abstract: Connolly, L. (2017). The endocrine disrupting potential of monosodium glutamate (MSG) on secretion of the glucagon-like-peptide-1 (GLP-1) gut hormone and GLP-1 receptor interaction. Toxicology Letters, 265, 97-105. DOI: 10.1016/j.toxlet.2016 Published in: Toxicology Letters Document Version: Peer reviewed version Queen's University Belfast -Research Portal: Link to publication record in Queen's University Belfast Research Portal Publisher rights © 2016 Elsevier Ltd. This manuscript version is made available un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…MSG was found to impair glucagon-like peptide (GLP-1) secretion in cell model, a peptide hormone that is important for β-cell growth, and insulin production [54]. In short term (3 h), secretion of GLP-1 was increased, but in chronic term (72 h), cytotoxicity was observed and there was a reduction in GLP-1 secretion [55].…”
Section: Genetic Aspects That Promote T2d: High-msg Intervention Studymentioning
confidence: 99%
“…MSG was found to impair glucagon-like peptide (GLP-1) secretion in cell model, a peptide hormone that is important for β-cell growth, and insulin production [54]. In short term (3 h), secretion of GLP-1 was increased, but in chronic term (72 h), cytotoxicity was observed and there was a reduction in GLP-1 secretion [55].…”
Section: Genetic Aspects That Promote T2d: High-msg Intervention Studymentioning
confidence: 99%
“…Elevated glutamate levels are associated with obesity and the administration of Bacteroides thetaiotaomicron, a glutamate fermenting bacteria, prevented weight gain in a DIO mouse model, underscoring a link between diet, GM, amino acids profiles, and weight regulation 55 . In addition, glutamate has shown to decrease production of GLP-1 by enteric L cells 56 .…”
Section: Interactions Between Diet and Gm Function In Obesitymentioning
confidence: 99%
“…We have previously shown that MSG decreases glucagon-like peptide 1 (GLP-1) secretion in a gut in vitro cellular model (Shannon et al, 2017), suggesting a possible mechanism by which MSG may affect glucose regulation and satiety responses.…”
Section: Introductionmentioning
confidence: 99%